2022
DOI: 10.3390/polym14050990
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultrasound Treatment on Barrier Changes of Polymers before and after Exposure to Food Simulants

Abstract: In this study, we investigated the impact of ultrasound treatment on barrier properties of linear low-density polyethylene (LLDPE) and acrylic/poly(vinylidene chloride) polypropylene (PPAcPVDC) - coated pouches intended for food packaging before and after exposure to food simulants. Packaging pouches were filled with two food simulants, namely ethanol (10% [v/v]) and acetic acid (3% [w/v]), in order to simulate food–packaging interaction and possible compound migration from packaging materials. Samples were su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…According to the thermodynamics of irreversible processes, water chemical potential difference is the driving force of the water transfer through the film (Anoua, Ramirez-Martinez, Cherblanc, & Benet, 2014). The resistance of barrier against water and gas transmission is one of the most important properties for packaging material, which affects the packed food products' overall quality and nutritional value (Ščetar, Daniloski, Tinjić, Kurek, & Galić, 2022). Therefore, the low barrier property of edible packaging can be considered suitable for food applications to enhance the quality and shelf life of food products (Kanatt et al, 2012;Kurt & Kahyaoglu, 2014).…”
Section: Barrier Propertiesmentioning
confidence: 99%
“…According to the thermodynamics of irreversible processes, water chemical potential difference is the driving force of the water transfer through the film (Anoua, Ramirez-Martinez, Cherblanc, & Benet, 2014). The resistance of barrier against water and gas transmission is one of the most important properties for packaging material, which affects the packed food products' overall quality and nutritional value (Ščetar, Daniloski, Tinjić, Kurek, & Galić, 2022). Therefore, the low barrier property of edible packaging can be considered suitable for food applications to enhance the quality and shelf life of food products (Kanatt et al, 2012;Kurt & Kahyaoglu, 2014).…”
Section: Barrier Propertiesmentioning
confidence: 99%
“…The effect that US has on packaging materials depends on their composition. On this, Scêtar et al [13] reported that polypropylene bags have better water vapor permeability and oxygen permeability properties compared to polyethylene bags. For this reason, the meat packed in 70 µm bags presented higher WHC values.…”
Section: Resultsmentioning
confidence: 96%
“…The use of high amplitudes and treatment times affect the properties of permeability, solubility and oxygen diffusion in the films [7] . Barrier properties can be significantly reduced in polyethylene-coated bags compared to polypropylene [13] . However, under optimal US conditions (2–6 min, 50 and 100 % amplitudes), the physical properties (thermal stability) of polypropylene films can be improved [13] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this non-invasive method could affect the food packaging material if used as an in-pack treatment. Therefore, knowledge about changes in barrier performance, mechanical properties, and the risk of migration of unwanted substances from the material into the food must be seriously considered and studied before applying ultrasound treatment to a food product [ 25 ].…”
Section: Short Overview Of Non-thermal Food Processing Techniques Com...mentioning
confidence: 99%